Analisis Perbandingan Perhitungan Penyusutan Aset Tetap Berdasarkan Standar Akuntansi Keuangan Dengan Peraturan Perpajakan Pada PDAM Wair Pu’an Kabupaten Sikka - Maria Fausta Valentin Lodan; Henrikus Herdi; Konstantinus Pati Sanga (Jurnal Mutiara Ilmu Akuntansi, 2023)
The purpose of this study is to analyze the comparison of depreciation expense between Financial Accounting Standards of Entities Without Public Accountability (SAK ETAP) and the Tax Law in PDAM Wair Puan Sikka Regency. The research method used is quantitative descriptive with data sources derived from secondary data. Analysis is carried out on depreciation expense using the straight-line method. The results of the analysis show a significant difference in the calculation of depreciation expense of fixed assets between SAK ETAP and the Tax Law. This research reveals that the depreciation expense calculation method applied by the Tax Law results in a greater depreciation expense than ETAP SAK, which has an impact on the accumulation of depreciation and the book value of fixed assets.